Segurança hídrica ecológica: fundamentos para um conceito jurídico - Silva, José Irivaldo Alves Oliveira (2020)
The present thesis had as a problem the following question: is it possible and necessary to structure a legal concept of water security based on an ecological paradigm? We adopted as a general objective to analyze how the regulation of the water cycle is legally approached in order to re-signify the concept of water security based on an ecological paradigm. As specific objectives we had the following: 1) to understand the legal protection of water, seeking to investigate how the essential factors for the water cycle are regulated, since in this relevant thesis the water cycle is considered for the construction of the most adequate legal content ecological water security; 2) analyze the place of the hydrological cycle in the rule of law; 3) verify the possibility of re-reading and readjusting the expression water security. The study was bibliographic and documentary, with access to various sources, books and articles, national and international, studies at the Federal University of Santa Catarina and at the Universitario del Agua y Ciencias Ambientales of the Universidad de Alicante, Spain, which are reference respectively in the approach of Ecological Law and in studies related to the multiple uses of water. We present five chapters in which we talk about the establishment of a water crisis, based on multiple causality, in an environment of water scarcity, environmental injustice and low equity. Therefore, it is possible to think of an Ecological Water Security as the availability of minimally sufficient water for all forms of life and which have a quality standard compatible with its use, with efforts being made to preserve hydrographic basins, recognizing and quantifying ecosystem services., taking into account the resilience of urban agglomerations, the preservation of all elements that have a direct relationship with the water cycle and, therefore, with the production of water, take care to reduce soil impermeability, as well as adopting technologies for the rational use of water in agriculture, without the application of pesticides, and in all industrial processes, adopting equity and environmental justice as pillars and applying reuse so that water can be maintained in the natural cycle as long as possible and in the urban cycle